Yang Sakral, Mitos, dan Kosmos: Analisis Kritis atas Fenomenologi Agama Mircea Eliade - Fiamrillah Zifamina, Ikhbar (LP2M UIN Sunan Kalijaga, 2022)
This article deals with the thought of Mircea Eliade in the phenomenology of religion. The method used in this study is the critical analysis for reviewing Eliade’s thinking about The Sacred, Myth, and Cosmos. The critical analysis of three concepts will lead to a context of phenomology of religion from Eliade. The urgency of this research lies in the implications of three concept in the discourse of religions studies, especially in the phenomenology of religion. This study concluded that: 1) Eliade’s concepts about The Sacred, Myth, and Cosmos indicates that phenomenology of religion from hiim was influenced by philosophy, especially phenomenological and hermeneutical, 2) The implications of the three concept in the phenomenology of religion from Eliade point to an approach that suggest the essence of meaning and interconnected of religious phenomenas, such as the supernatural-natural, spiritual-material, or sacred-profane. [Artikel ini membahas tentang pemikiran Mircea Eliade dalam fenomenologi agama. Metode yang digunakan dalam penelitian ini adalah analisis-kritis untuk meninjau pemikiran Eliade tentang Yang Sakral, Mitos dan Kosmos. Analisis kritis atas ketiga konsep tersebut akan mengarah pada konteks fenomenologi agama dari Eliade. Sehingga dalam hal ini, urgensi penelitian ini terletak pada implikasi ketiga konsep tersebut pada diskursus studi agama-agama, khususnya fenomenologi agama. Penelitian ini menyimpulkan bahwa : 1) Konsep Eliade tentang Yang Sakral, Mitos dan Kosmos menunjukkan fenomenologi agama Eliade dipengaruhi oleh filsafat, khususnya fenomenologi dan hermeneutika, 2) Implikasi ketiga konsep tersebut dalam fenomenologi agama Eliade mengarah pada pendekatan yang menujukkan esensi makna dan saling terkaitnya fenomena-fenomena agama, seperti yang supernatural-natural, spiritual-material, maupun sakral-profan.]